KALIBRASI PARAMETER MODEL HEC-HMS UNTUK MENGHITUNG ALIRAN BANJIR DAS BENGKULU - Tunas, Gede (MEKTEK, 2005)
HEC-HMS is an hydrology modelÂ for use in analyzing a watershed system in order to predict the hydrologic response of the system to a user defined rainfall event. To obtain the optimal parameter value, HEC-HMS model must be calibrated by adjusting model parameter values untilÂ model results match historical data. This research would try to calibrate HEC-HMS parameter model in Bengkulu Hulu Watershed. Parameter values are adjusted by the search methods and the hydrograph and objective function for the target element are recomputed. The result of simulation shows that the optimal parameter value for several optimization which stated by function value have 5.8 % error (RMS error type)